Evaluation of different approaches to enhancing arteriogenesis using isolated monocytes and GM-CSF treatment in an ischemic mouse hind limb model - Szymanski, Silvia; Justus Liebig University Giessen (My University, 2006)
Arteriogenesis, the growth of collateral arteries as a compensatory mechanism afterocclusion of a major artery, is a complex process in which peripheral blood cells have beenproposed to be involved. This study was concentrated on the role of monocytes, effects ofdifferent monocyte concentrations in the blood and effects of monocyte pre-treatment withspecific substances on the enhancement of collateral artery growth.For this purpose, a mouse ischemic hind limb model was established on the BALB/cgenetic background. After acute femoral artery occlusion, mice received intravenousinjections of monocytes in several concentrations, isolated from donor littermates using a cellsorter. Moreover, we pre-treated monocytes with a synthetic prostaglandin (Cicaprost) or withgranulocyte-macrophage colony-stimulating factor (GM-CSF). We also evaluated if treatmentof operated mice with GM-CSF alone could enhance collateral artery growth and if acombination of monocyte injections with GM-CSF had a synergistic effect. Pedal blood flowrecovery in mice was measured using the laser Doppler imaging technique immediately afteroperation and on postoperative day 3, 7, 14 and 21. Moreover, pedal hemoglobin oxygensaturation was estimated at the same time points. Functional recovery of the foot movementwas observed during the whole trial period. On the day 21 after the operation, post-mortemangiogramms were performed and adductor muscles were harvested for the morphometricalanalysis. The hemodynamic data showed that injection of monocytes had a concentrationdependenteffect in enhancing of blood flow recovery in the operated foot. Seven days afterfemoral artery ligature, the blood flow recovery (right-to-left ratio) was only 0.21 ± 0.02 incontrol mice and significantly higher in mice which had obtained monocyte injections (0.30 ±0.04 in mice with 2x105 monocytes injected, p<0.05 and 0.33 ± 0.04 in mice with 3x105monocytes injected, p<0.01). Morphometrical analysis of adductor muscles of operated andnon-operated hind limbs showed that total collateral area ratio, which was obtained as aparameter to estimate collateral artery size, increased markedly in monocyte-treated micecompared to controls (2.37 ± 0.12 in mice with 2x105 monocytes injected; p<0.01 and 2.66 ±0.12 in mice with 3x105 monocytes injected; p<0.01 vs. 1.88 ± 0.08 in controls). Pretreatmentof monocytes with Cicaprost or GM-CSF did not enhance their arteriogenicproperties. Administration of GM-CSF via intraperitoneal injections did not enhance theblood flow recovery, however the combination of GM-CSF and monocyte injections had a moderate synergistic effect reflected in blood flow measurements (R/L ratio on day 7 was0.40 ± 0.05 which was the highest ratio of all experimental groups of animals; p<0.01), aswell as in morphometrical analysis of adductor muscles (total collateral area ratio was 3.32 ±0.14; p<0.01)Our results show that monocytes/macrophages play a crucial role in enhancement ofcollateral artery growth. In addition, a combination of GM-CSF treatment and monocyteinjections allows administration of smaller concentrations of therapeutics and results in asuperior blood flow recovery. Our study suggests a possibility of using cellular approaches forthe treatment of vascular occlusive diseases.

Als Arteriogenese wird das kompensatorische Wachstum von Kollateralgefäßen nacharteriellen Verschlüssen bzw. chronischen Stenosen bezeichnet. Aufgrund von Ergebnissen frühere Studien vermutete man, dass an den komplexen Prozessen, die dieses Wachstum charakterisieren, zirkulierende Blutzellen, vor allem Leukozyten, beteiligt sind. Zielsetzung dieser Studie war es deshalb, die Rolle der Monozyten, die Effekte unterschiedlicher Blutmonozytenkonzentrationen und den Einfluss einer Vorbehandlung der Monozyten mit spezifischen Substanzen auf die Arteriogenese zu untersuchen.Hiezu wurde das Hinterlauf-Ischämien-Modell in der Maus (BALB/c) verwendet. Nach dem Verschluss der Arteria femoralis erhielten die Mäuse in unterschiedlichenKonzentrationen intravenöse Injektionen von Monozyten, die zuvor aus genetisch identischenMäusen mittels cell sorter isoliert wurden. Weitere Versuchsgruppen wurden mit Monozytenbehandelt, die zuvor mit einem synthetischen Prostaglandinen (Cicaprost) bzw. mit demGranulozyten-Makrophagen-Kolonie-stimulierenden Faktor (GM-CSF) vorbehandelt wurden. Es wurde ebenfalls untersucht, ob Injektionen von GM-CSF das Kollateralgefäßwachstumnach Okklusion der Femoralarterie verstärken und ob eine Kombinationstherapie aus GMCSF-Injektionen und Monozytentransplantationen einen zusätzlichen stimulativen Effekthaben. Sofort nach der Operation als auch an den Tagen 3, 7, 14 und 21 wurden Laserdoppler-Untersuchungen zur Bestimmung der Wiederherstellung der pedalen Durchblutungdurchgeführt. Zusätzlich wurde die Sauerstoff-Sättigung im Hämoglobin in den distalenGefäßen bestimmt. Als funktioneller Parameter während des Beobachtungszeitraumes wurdedie aktive Bewegung der Hinterläufe quantifiziert. Drei Wochen nach Versuchsbeginn wurdedas Kollateralgefäßsystem durch Angiographien post mortem dargestellt und Gewebeprobenzur morphometrischen Analyse konserviert. Die hämodynamischen Daten zeigen, dass die Monozyteninjektionen einendosisabhängigen positiven Effekt auf das Kollateralgefäßwachstum hatten. Am siebten Tagnach dem Verschluss der Arteria femoralis war der pedale Blutfluss (rechts-zu-links Rate) inKontrollmäusen nur 0,21 ± 0,02 und signifikant höher in Mäusen, die Monozyten injiziertbekommen haben (0,30 ± 0,04 in Mäusen, die 2x105 Monozyten bekommen haben; p<0,05und 0,33 ± 0,04 in Mäusen, die 3x105 Monozyten bekommen haben; p<0,01). Morphometrische Analysen der Adduktoren von den operierten und nicht operiertenHinterläufen ergaben, dass die gesamte Kollateralflächenrate, die als Parameter zurBewertung der Kollateralgefäßgröße diente, war in Monozyten behandelten Mäusen verglichen mit den Kontrollen deutlich erhöht (2,37 ± 0,12 in Mäusen, die 2x105 Monozytenbekommen haben; p<0,01 und 2,66 ± 0,12 in Mäusen, die 3x105 Monozyten bekommenhaben; p<0,01 vs. 1,88 ± 0,08 in Kontrollen). In Gegensatz hierzu hatten dieVorbehandlungen der Monozyten mit Cicaprost oder GM-CSF keinen weiteren arteriogenenEffekt. Des weiteren verstärkten die Injektionen von GM-CSF die Wiederherstellung derDurchblutung nicht, auch wenn die Kombinationstherapie von GM-CSF und Monozyten-Injektionen einen moderaten synergistischen Effekt hatte (R/L Rate am Tag 7 war 0,40 ±0,05, der höchste Wert von allen Versuchsgruppen; p<0,01). Diese Ergebnisse wurden durchhistologische Untersuchungen der Adduktorenmuskulatur von operierten und nicht operiertenHinterläufen erhärtet (die gesamte Kollateralflächenrate war 3,32 ± 0,14; p<0,01). Die Ergebnisse zeigen, dass die Monozyten/Makrophagen eine wichtige Rolle in derStimulierung des Kollateralgefäßwachstums spielen. Außerdem ist es möglich durch dieKombination von GM-CSF- mit Monozyten-Injektionen die Konzentrationen derTherapeutika gegenüber der Einzeldosierungen zu reduzieren, wobei trotzdem die bestenErgebnisse erzielt werden konnten. In dieser Studie wurden die Grundlagen zum Einsatzzellulärer Therapeutika in der Behandlung von Herz-Kreislauf-Erkrankungen geschaffen.
Keywords: ddc:610